Strategy to Increase Added Value of Coffee Commodity for Bentenge Coffee in Mallawa District Maros Regency - Hikmah Maulidyanti; Marhawati Marhawati; Nurdiana Nurdiana; Muh. Ihsan Said; Rahmatullah Rahmatullah (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This study aims to describe the internal factors and external factors that influence the increase in the added value of coffee commodities at Bentenge Coffee in Mallawa District, Maros Regency and determine strategies that can be applied to increase the added value. This research is a type of qualitative research with a descriptive approach with informants selected based on the determination of informant criteria that have been designed previously. The instrument used is a semi-structured research instrument which is validated by the instrument validator. The results of the study show that the strategy that can be implemented in increasing the added value of the Bentenge Coffee business is an aggressive strategy, namely 1) Improving the quality of human resources to take advantage of science and technology developments and supporting a more varied diversification of processed coffee products, 2) Improving the quality and distinctive taste so that it can take advantage of trends drinking coffee and a wide market reach, and 3) Utilizing the availability of raw materials, production processes with more sophisticated tools and technology to add product variants and improve product packaging so that they are better known as local products that are in demand by consumers.